Do hearing threshold levels in workers of the furniture industry reflect their exposure to noise? - Małgorzata Pawlaczyk-Łuszczyńska; Adam Dudarewicz; Norman Czaja; Alicja Bortkiewicz (Nofer Institute of Occupational Medicine, 2016)
Background: The aim of the study was to analyze the hearing status of employees of a furniture factory with respect to their exposure to noise and the presence of additional risk factors of noise-induced hearing loss (NIHL). Material and Methods: Noise measurements, questionnaire survey and assessment of hearing, using pure tone audiometry, were carried out in 50 male workers, aged 20-57 years, directly employed in the manufacture of furniture. The actual workers' hearing threshold levels (HTLs) were compared with the predictions calculated according to PN-ISO 1999:2000 based on age, gender and noise exposure. Results: Workers under study were exposed to noise at daily noise exposure levels of 82.7-94.8 dB (mean: 90.9 dB) for a period of 3-14 years. In all subjects, mean HTL at 500 Hz, 1000 Hz, 2000 Hz and 4000 Hz did not exceed 25 dB. Nevertheless, high frequency notches were found in 11% of audiograms. The actual workers' HTLs at 3000-6000 Hz were similar to those predicted using PN-ISO 1999:2000. There were statistical significant differences between HTLs in subgroups of people with higher (> 78 mm Hg) and lower (≤ 78 mm Hg) diastolic blood pressure, smokers and non-smokers, and those working with organic solvents. Hearing loss was more evident in subjects affected by the additional risk factors specified above. Conclusions: The results confirm the need to consider, in addition to noise, also some other NIHL risk factors, such as tobacco smoking, elevated blood pressure, and co-exposure to organic solvents when estimating the risk of NIHL and developing the hearing conservation programs for workers. Med Pr 2016;67(3):337-351